The Effect of Zophobas Morio Superworms as the Agent towards Polystyrene Biodegradation to Reduce Plastic Waste Pollution - BIN MOHD ROSDI, MUHAMMAD AIDIL ASHRAF; BINTI HASHIM, NOR HASLINA BINTI HASHIM; BINTI MOHAMAD FUZI, SITI FATIMAH ZAHARAH BINTI MOHAMAD FUZI (Progress in Engineering Application and Technology, 2025)
Plastic waste pollution, particularly polystyrene (PS), presents significant environmental challenges due to its durability and resistance to degradation. This study investigates the potential of Zophobas morio larvae, commonly known as superworms, in biodegrading polystyrene under various conditions. Utilizing their unique gut microbiota, these larvae were subjected to controlled laboratory experiments to determine the optimal conditions for plastic biodegradation. Key variables included temperature (21°C–23°C and 28°C–30°C), diet composition (PS, HDPE, LDPE, and mixed diets), and exposure duration (10 and 13 days). The results highlighted that superworms can effectively degrade polystyrene, with the highest efficiency achieved at lower laboratory temperatures (21°C–23°C) and a mixed diet at 13 days. The degradation was evaluated through weight loss measurements and larval health observations. Data analyses confirmed significant differences in degradation efficiency across the tested conditions. These findings underscore the potential of Zophobas morio larvae as a cost-effective, eco-friendly solution for managing plastic waste, offering a sustainable alternative to conventional methods such as landfilling and incineration. By optimizing conditions like diet and temperature, this research contributes to the growing field of biological waste management and offers promising insights into reducing plastic pollution's environmental footprint.